2013
DOI: 10.1177/1087057113484803
|View full text |Cite
|
Sign up to set email alerts
|

A Kinome-Wide siRNA Screen Identifies Multiple Roles for Protein Kinases in Hypoxic Stress Adaptation, Including Roles for IRAK4 and GAK in Protection against Apoptosis in VHL–/– Renal Carcinoma Cells, Despite Activation of the NF-κB Pathway

Abstract: Hypoxia induces changes to cancer cells that make them more resistant to treatment. We have looked at signaling pathways that facilitate these changes by screening the human kinome for effects on hypoxic responses in SW480 colon cancer cells. Hits identified in the screen were examined for effects on multiple molecular responses to hypoxia, including the endoplasmic reticulum stress and DNA damage responses in colon, melanoma, and renal cancer lines. To validate the hits from the small interfering RNA studies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…). Interestingly, others have reported that stable short hairpin RNAs against Mirk(dyrk1B) prevented the A598 renal carcinoma cell line from forming spheroid cultures (26), consistent with our observations of the loss of spheroid structure with Mirk kinase inhibition. The Mirk/dyrk1B inhibitor EHT5372 caused a progressive loss in tumor cell numbers: 50% after 6 days, 60% after 8 days, 80% after 15 days, and 92% after 21 days (Fig 3A…”
Section: Resultssupporting
confidence: 92%
“…). Interestingly, others have reported that stable short hairpin RNAs against Mirk(dyrk1B) prevented the A598 renal carcinoma cell line from forming spheroid cultures (26), consistent with our observations of the loss of spheroid structure with Mirk kinase inhibition. The Mirk/dyrk1B inhibitor EHT5372 caused a progressive loss in tumor cell numbers: 50% after 6 days, 60% after 8 days, 80% after 15 days, and 92% after 21 days (Fig 3A…”
Section: Resultssupporting
confidence: 92%
“…Thus the Mirk kinase inhibitor reduced the number of Panc1 cells in the spheroids, consistent with the cells in the outside layers dying of apoptosis and reducing spheroid volume. Interestingly, others have reported that stable short hairpin RNAs against Mirk/dyrk1B prevented the A498 renal carcinoma cell line from forming spheroid cultures [ 26 ]. Disruption of spheroids to single cells is a step in their dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…Functional genetic screens provide an unbiased and powerful means of identifying genes responsible for any phenotype that can be measured experimentally. Unbiased RNAi screens have identified genes that influence the survival of organisms and cells under various stresses [ 33 36 ]. These studies provide a foundation for using RNAi screens to uncover genes involved in TME-relevant stress responses, but so far have not been applied genome-wide to identify genes that modulate the survival of cancer cells under hypoxia or lactic acidosis.…”
Section: Introductionmentioning
confidence: 99%